CAR T-cells for colorectal cancer immunotherapy: Ready to go? - Ghazi, Bouchra; El Ghanmi, Adil; Kandoussi, Sarah; Ghouzlani, Amina; Badou, Abdallah (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T-cells represent a new genetically engineered cell-based immunotherapy tool against cancer. The use of CAR T-cells has revolutionized the therapeutic approach for hematological malignancies. Unfortunately, there is a long way to go before this treatment can be developed for solid tumors, including colorectal cancer. CAR T-cell therapy for colorectal cancer is still in its early stages, and clinical data are scarce. Major limitations of this therapy include high toxicity, relapses, and an impermeable tumor microenvironment for CAR T-cell therapy in colorectal cancer. In this review, we summarize current knowledge, highlight challenges, and discuss perspectives regarding CAR T-cell therapy in colorectal cancer.